2013
DOI: 10.1128/jb.00410-13
|View full text |Cite
|
Sign up to set email alerts
|

The Essential Function of Genes for a Hydratase and an Aldehyde Dehydrogenase for Growth of Pseudomonas sp. Strain Chol1 with the Steroid Compound Cholate Indicates an Aldolytic Reaction Step for Deacetylation of the Side Chain

Abstract: In the bacterial degradation of steroid compounds, the enzymes initiating the breakdown of the steroid rings are well known, while the reactions for degrading steroid side chains attached to C-17 are largely unknown. A recent in vitro analysis with Pseudomonas sp. strain Chol1 has shown that the degradation of the C 5 acyl side chain of the C 24 steroid compound cholate involves the C 22 intermediate 7␣,12␣-dihydroxy-3-oxopregna-1,4-diene-20S-carbaldehyde (DHOPDCA) with a terminal aldehyde group. In the presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
79
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(82 citation statements)
references
References 45 publications
3
79
0
Order By: Relevance
“…This activity is required for salvaging cholesterol-24-oic acids that are formed as a result of CoA ester hydrolysis during β-oxidation or that are formed through an alternate pathway ( vide infra ) (Holert et al, 2013a). …”
Section: Cholesterol Side Chain Metabolismmentioning
confidence: 99%
See 2 more Smart Citations
“…This activity is required for salvaging cholesterol-24-oic acids that are formed as a result of CoA ester hydrolysis during β-oxidation or that are formed through an alternate pathway ( vide infra ) (Holert et al, 2013a). …”
Section: Cholesterol Side Chain Metabolismmentioning
confidence: 99%
“…strain Chol1, it has been proposed on the basis of gene knockout and metabolite studies, and assays in cell lysates that cleavage of the 24-oyl-CoA intermediate produces an aldehyde metabolite rather than a thioester via a classical β-oxidation pathway. This cleavage is catalyzed by an aldolase (shy) that is homolgous to Ltp3 from R. rhodochrous DSM 43269 (Holert et al, 2013a, Holert et al, 2013b). The aldehyde is then oxidized to the carboxylic acid by an aldehyde dehydrogenase (sad) and esterified by a CoA ligase.…”
Section: Cholesterol Side Chain Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…CasI likely functions in reassimilation of the metabolites which accumulate when RHA1 grows on cholate (27). CasI orthologs likely function in further degradation of an intermediate resulting from the above-mentioned aldolytic cleavage of the cholate side chain by Proteobacteria (12,24). It is unclear whether such aldolytic cleavage occurs in Actinobacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Holert et al recently showed evidence for degradation of the cholate side chain in Proteobacteria via a variation of ␤-oxidation, in which an acetyl-CoA moiety is removed by aldolytic, rather than thiolytic, cleavage (12,24). The resulting aldehyde is proposed to be oxidized to an acid and reactivated by CoA thioesterification for another round of ␤-oxidation.…”
mentioning
confidence: 99%